ZERO EMISSION AN ANALYSIS OF ILLEGAL MINING AS A NON-PROCEDURAL EXPLOITATION OF THE LAW - Ginesha Prema Rajeshvari Linggar Putri; Paulinus Verynanda; Rini Puspita Ayu; Sania Teresa Sinaga; Sethya Sahra Intan Salampessy; Thia Vanesia (President University, 2023)
Zero Emission also known as Net Zero Emission is a step in pursuing Indonesia's pollution-free mission. Efforts are made to neutralize pollution caused by human activities, so an absorption resource is needed. However, these absorptive resources, namely forests, are damaged due to illegal mining activities because they are non-procedural so mining activities impact deforestation. In writing this journal, a qualitative normative legal approach was used with secondary data and other relevant legal sources to gain insight into the legal aspects of illegal mining. The purpose of writing is to criticize law enforcement against illegal mining activities in achieving the mission of a pollution-free Indonesia.Keywords:Zero Emission; Illegal Mining; Non-Procedural Exploitation of Law